Transesterification of babassu oil catalyzed by Burkholderia cepacia encapsulated in sol-gel matrix employing protic ionic liquid as an additive - Oliveira, Maria Vanessa Souza; Da Rós, Patrícia Caroline Molgere; Mattedi, Silvana; Castro, Heizir Ferreira; Soares, Cleide Mara Faria; Lima, Ílvaro Silva (Acta Scientiarum. Technology, 2014)
Enzymatic transesterification from non-edible vegetable oil (babassu oil) and ethanol is provided. A set of seven experiments featuring a full 22 factorial design with three central points and different combinations of molar ratio and temperature as independent variables was employed. Transesterification reactions were catalyzed by Burkholderia cepacia lipase encapsulated in a hydrophobic matrix obtained by the sol-gel technique using protic ionic liquid (N-methylmonoethanolamine pentanoate) as additive and with conventional heating (40 - 56Â°C). Ethyl esters highest yield (51.90%) was obtained by experimental design with 1:7 molar ratio (oil:alcohol) and temperature at 40Â°C during 48h reaction. The process with a 5-fold increase of enzymatic load provided 98.69% ethyl esters yield with 4.29 mm2 s-1 viscosity Â